A contrastive study on metonymy in English and Vietnamese / Trần Phương Thanh; NHDKH Assoc. Prof. Dr. Vo Dai Quang - Trần, Phương Thanh
This study provides a contrastive analysis of metonymy in English and Vietnamese. Theoretically, this is a systematic study on the metonymy as a transference mode of meaning in English. Furthermore, it is aimed at finding the similarities and differences in the ways of using metonymy in English and Vietnamese. Practically, this study is intended to help Vietnamese learners of English to have more knowledge of metonymy as a transference mode of meaning in English and Vietnamese. Therefore, they will get use of the knowledge of metonymy to enhance their vocabulary. Contrastive and descriptive analysis is the main methods based on the data collected from many books, websites and previous studies. The findings of the study provide evidence that metonymy is very widely used in both spoken and written language. Using this mode of transference of meaning brings more rhetorical color for the language. English and Vietnamese share some similarities and differences in using metonymy. The differences in the ways of using metonymy between English and Vietnamese are based on the different culture and history. The results of the study are significant. As for teachers, this research is a good reference of the use of metonymy as a figure of speech. As for students, they will have better understanding of the metonymy and will have better result in learning English in general and learning vocabulary in particular. As for translators, they will be more aware of the similarities and differences of metonymy in both two languages.